DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Shamsuddinova Ruqiyaxon; Jalolova M (TADQIQOTLAR, 2025)
Annotation: This article explores the key difficulties faced by teachers when teaching foreign languages to young learners. It examines challenges such as short attention spans, limited cognitive skills, mixed abilities, classroom management, lack of  motivation,  limited  exposure  outside  the  classroom,  pronunciation  and  listening difficulties,  and  assessment  issues.  The  article  also  offers  practical  suggestions  for overcoming  these  challenges  and  highlights  the  importance  of  a  supportive  and engaging learning environment.